GLOBALNE STRATEGIE REKLAMOWE W PRZESTRZENI WIELOKULTUROWEJ - Duda, Aneta (Wydział Prawa i Administracji UAM, 2007)
Studies of international advertising continue to receive much attention by entrepreneurs as well as scientists. Global versus local advertising is something that multinational marketers have been wrestling with over thirty years. On the one hand George Murdock’s or Claude Lévi-Strauss’ categories of culture universalis are used to prove that peoples wants, needs, and values would eventually become so similar that uniform advertising campaigns across cultures would be justified. On the other hand Edward Hall, Martin Gannon, Geert Hofstede or Charles Hampden-Turner and Alfons Trompenaars’ theories are gaining in popularity for identification of cultural differences. As discussed in this paper, there are serious concerns about global advertising in the light of cultural uniformity and erasure o f international diversity. Would the use of one campaign for the globe eventually erode the multiplicity o f cultural perspectives? Is standardized advertising, which ignores local culture, an effective means for building powerful communication? The author believes that there is not one adequate global language with which to reach all consumers. Universal, global strategies are memoryless, superficial and always a compromise when we resign from cultural invention and diversity.
GLOBAL ADVERTISING STRATEGIES IN MULTICULTURAL SPACE